2017
DOI: 10.1038/s41467-017-01388-5
|View full text |Cite
|
Sign up to set email alerts
|

PLCγ-dependent mTOR signalling controls IL-7-mediated early B cell development

Abstract: The precise molecular mechanism underlying the regulation of early B cell lymphopoiesis is unclear. The PLCγ signaling pathway is critical for antigen receptor-mediated lymphocyte activation, but its function in cytokine signaling is unknown. Here we show that PLCγ1/PLCγ2 double deficiency in mice blocks early B cell development at the pre-pro-B cell stage and renders B cell progenitors unresponsive to IL-7. PLCγ pathway inhibition blocks IL-7-induced activation of mTOR, but not Stat5. The PLCγ pathway activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 72 publications
1
32
0
1
Order By: Relevance
“…Immature B cells then migrate to the periphery where they further differentiate into various mature B cell subsets that play distinct roles. The survival and maturation of B cells are dependent on the strength of tonic BCR signal (50, 51). Studies from our group, Honjo et al and Nguyen et al revealed that FcμR deficiency did not significantly affect B cell development, but altered the numbers of different B cell subsets (32, 33).…”
Section: Fcμr In B Cell Development and Maturationmentioning
confidence: 99%
“…Immature B cells then migrate to the periphery where they further differentiate into various mature B cell subsets that play distinct roles. The survival and maturation of B cells are dependent on the strength of tonic BCR signal (50, 51). Studies from our group, Honjo et al and Nguyen et al revealed that FcμR deficiency did not significantly affect B cell development, but altered the numbers of different B cell subsets (32, 33).…”
Section: Fcμr In B Cell Development and Maturationmentioning
confidence: 99%
“…PLCG2 is involved in alleviating ROS levels and is closely associated with OS [ 26 , 27 ]. Other studies found that PLCG2 regulated mTOR through the diacylglycerol/protein kinase C signaling branch, thereby affecting the proliferation and apoptosis of B cells [ 62 ]. PKA is cAMP-dependent protein kinase, which played a crucial role in inducing cell signal response and regulating the signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear and cytoplasmic PLCγ1 are also implicated in the regulation of the lymphoid lineage, particularly in T cells, but with increasing studies on early B cells [108,109], PLCγ1 seems to be essential for the regulation of T cells activation and differentiation, through the classical T cell receptor (TCR) signaling pathway. In addition, PLCγ1 is also involved in the context of signaling initiated by both growth factors and non-receptor tyrosine kinases, such as epidermal growth factor Indeed, in recent years, erythropoiesis-stimulating agents (ESAs) were used as first-line therapy in most patients with lower-risk non-del(5q) MDS, mainly with the aim of managing anemia and the prevention of transfusion-related complications which is associate with secondary organ damage, decreased survival, and leukemic progression [95,96].…”
Section: Plcγ1mentioning
confidence: 99%
“…Nuclear and cytoplasmic PLCγ1 are also implicated in the regulation of the lymphoid lineage, particularly in T cells, but with increasing studies on early B cells [108,109], PLCγ1 seems to be essential for the regulation of T cells activation and differentiation, through the classical T cell receptor (TCR) signaling pathway. In addition, PLCγ1 is also involved in the context of signaling initiated by both growth factors and non-receptor tyrosine kinases, such as epidermal growth factor and hepatocyte growth factor [89,110,111].…”
Section: Plcγ1mentioning
confidence: 99%